Tumour mutational burden: primary versus metastatic tissue creates systematic bias - Desiree Schnidrig; Samra Turajlic; Kevin Litchfield (Immuno-Oncology and Technology, 2019)
Tumour mutational burden (TMB) has emerged as a reproducible biomarker to predict immunotherapy response across multiple cancer types. However, a key aspect of TMB measurement that is often overlooked is the source of tissue sample used, which creates a potential for systematic bias. The predominant source is either primary or metastatic tumour tissue. Primary tumours are more heterogeneous and reflect a longer period of tumour evolution, whereas metastases tend to have a more monoclonal structure and potentially different TMB scores. Studies to date measuring TMB have used a heterogeneous set of primary and metastatic tissues, which may explain some of the variability in predictive TMB values across studies. This paper presents data to show that there is a systematic difference whereby metastatic TMB is biased towards higher values than primary TMB (36% higher, paired Wilcoxon, P = 0.0008). However, effectiveness in predicting overall survival during immune checkpoint inhibitor therapy was found to be equivalent between primary and metastatic TMB. We highlight that lower TMB in primary tissue may be important in cases with borderline primary TMB, where assaying metastatic TMB may lead to a different treatment stratification result. As TMB progresses towards clinical implementation, particularly in classically non-immunogenic tumour types, it is important to have better curated trials with either the source of tissue annotated or a prospective study assessing concordance between paired primary and metastatic tissue.